2017
DOI: 10.1111/liv.13581
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein induces hepatic steatosis via Sirt1‐dependent pathway

Abstract: Sirt1 mediates hepatitis C virus core protein 1b-induced hepatic steatosis by regulation of PPARγ2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The impact of HCV on the development of NAFLD is well established, however, the underlying mechanism by which HBV mediates hepatic steatosis has not been clearly studied. Currently, studies have shown that the risk of NAFLD was significantly lower in HBV‐infected patients than in uninfected controls .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of HCV on the development of NAFLD is well established, however, the underlying mechanism by which HBV mediates hepatic steatosis has not been clearly studied. Currently, studies have shown that the risk of NAFLD was significantly lower in HBV‐infected patients than in uninfected controls .…”
Section: Discussionmentioning
confidence: 99%
“…Properly sized tissues were embedded in OCT compound, frozen at -80˚C and prepared for cryosectioning (Sakura Finetek USA, Inc.), and the thickness of the sections was maintained at 12-15 µm. Oil Red O staining was performed using a previously described method ( 20 ). The stained sections would be kept in 4˚C.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, increasing BAT activation and inducing beiging in WAT could be an effective therapeutic strategy for obesity and related diseases. SIRT1, a nuclear NAD + -dependent protein deacetylase (Landry et al, 2000) that belongs to the sirtuin family (referred to as Sirt1 to Sirt7) (Frye, 2000), plays a vital role in regulating transcription in various key metabolites (Zhang et al, 2018). Many studies have reported that SIRT1 can enhance BAT function and regulate metabolism (Xu et al, 2013;Boutant et al, 2015;Chalkiadaki and Guarente, 2012).…”
Section: Introductionmentioning
confidence: 99%